STUDIES OF INNATE IMMUNITY PARAMETERS (TLR2, TLR4 AND HBD1) OF URETHERAL MUCOUS EPITHELIUM IN CHRONIC BACTERIAL CYSTITIS - O. A. Svitich (SPb RAACI, 2016)
The study for quantitation of TLR2, TLR4 and HBD-1 gene expression in urethral mucosal epithelium from women with chronic bacterial cystitis and healthy females. Materials and methods: RNA was extracted from the samples of urethral mucosa followed by RT-PCR. Results: increased expression of TLR2, TLR4 (respectively, 6.9-, 2.6-fold), along with 13.6-fold decrease in HBD-1 was revealed in women with chronic bacterial cystitis, as compared with appropriate parameters in normal women. Six months later, after combined therapy with autologous immunopeptide complex, TLR2, TLR4 и HBD1 expression levels proved to be near-normal in the patients, being similar to those in healthy females. Conclusion: Imbalanced expression of genes controlling innate immunity was revealed in urethral mucosa of the patients with chronic cystitis, thus increasing risk for urinary tract infections.